Epidemiology of Cervical Spine Injuries in High School Athletes Over a Ten‐Year Period. Issue 4 (12th September 2017) - Meron, Adele; McMullen, Christopher; Laker, Scott R.; Currie, Dustin; Comstock, R. Dawn
Abstract: Background: More than 7 million athletes participate in high school sports annually, with both the benefits of physical activity and risks of injury. Although catastrophic cervical spine injuries have been studied, limited data are available that characterize less‐severe cervical spine injuries in high school athletes. Objective: To describe and compare cervical spine injury rates and patterns among U.S. high school athletes across 24 sports over a 10‐year period. Design: Descriptive epidemiology study. Setting: National sample of high schools participating in the High School Reporting Information Online injury surveillance system. Participants: Athletes from participating schools injured in a school sanctioned practice, competition, or performance during the 2005–2006 through 2014–2015 academic years. Methods: Cervical spine injury data captured by the High School Reporting Information Online system during the 10‐year study period were examined. Cervical spine injury was defined as any injury to the cervical spinal cord, bones, nerves, or supporting structures of the cervical spine including muscles, ligaments, and tendons. Main Outcome Measurements: Cervical spine injury rates, diagnoses, mechanisms, and severities. Results: During the study period, 1080 cervical spine injuries were reported during 35, 581, 036 athlete exposures for an injury rate of 3.04 per 100, 000 athlete exposures. Injury rates were highest in football (10.10), wrestling (7.42), and girls' gymnastics (4.95). Muscle injuries were most common (63.1%), followed by nerve injuries (20.5%). A larger proportion of football injuries were nerve injuries compared with all other sports (injury proportion ratio 3.31; confidence interval 2.33‐4.72), whereas in boys' ice hockey fractures represented a greater proportion of injuries compared with all other sports (injury proportion ratio 7.64; confidence interval 2.10‐27.83). Overall, the most common mechanisms of injury were contact with another player (70.7%) and contact with playing surface (16.1%). Conclusions: Cervical spine injury rates and patterns vary by sport and gender. Characterizing these differences is the first step in developing effective, evidence‐based prevention guidelines. Level of Evidence: IV